Regional differences in access to acute ischaemic stroke care and patient outcomes. Issue 8 (6th August 2020) - Dwyer, Mitchell; Peterson, Greg; Gall, Seana; Kinsman, Leigh; Francis, Karen; Ford, Karen; Castley, Helen; Kitsos, Alex; Hilliard, Tamsin; English, Jennifer
Abstract: Background: Advances in stroke management such as acute stroke units and thrombolysis are not uniformly distributed throughout our population, with rural areas being relatively disadvantaged. It remains unclear, however, whether such disparities have led to corresponding differences in patient outcomes. Aims: To describe the regional differences in acute ischaemic stroke care and outcomes within the Australian state of Tasmania. Methods: A retrospective case note audit was used to assess the care and outcomes of 395 acute ischaemic stroke patients admitted to Tasmania's four major public hospitals. Sixteen care processes were recorded, which covered time‐critical treatment, allied health interventions and secondary prevention. Outcome measures were assessed using 30‐day mortality and discharge destination, both of which were analysed for differences between urban and rural hospitals using logistic regression. Results: No patients in rural hospitals were administered thrombolysis; these hospitals also did not have acute stroke units. With few exceptions, patients' access to the remaining care indicators was comparable between regions. After adjusting for confounders, there were no significant differences between regions in terms of 30‐day mortality (odds ratio (OR) = 0.99, 95% confidence interval (CI) 0.46–2.18) or discharge destination (OR = 1.24, 95% CI 0.81–1.91). Conclusions: With the exception of acute stroke unit care and thrombolysis, acute ischaemic stroke care within Tasmania's urban and rural hospitals was broadly similar. No significant differences were found between regions in terms of patient outcomes. Future studies are encouraged to employ larger data sets, which capture a broader range of urban and rural sites and record patient outcomes at extended interval.